COVID 19-mass gathering events and attendee safety protocol for turbulent times - Hutton, A.; Robertson, M.; Ranse, J. (CAUTHE 2021: Transformations in Uncertain Times: Future perfect in tourism, hospitality and events : Proceedings of the 31st Annual Conference, 2021)
This paper forwards a psychosocial perspective of event safety management. In a time of social and economic upheaval - exasperated by the Covid-19 pandemic, safety has become increasingly significant in the vocabulary of researchers, managers, funding agencies and public bodies involved in the provision of events. The work documented here appraises the role of those with responsibility in managing people and their safety at mass gathering events, i.e. police, event managers and medical teams. It does so through a focus group review process with members from each of the aforementioned groups, and with reference to the analytical frame of the Ottawa Charter (1986). The work contributes to knowledge of event and crowd management, advancing the concept of transformative civic responsibilities while reframing aspects of the event experience to encourage trust and resilience in both attendees and host populations. The work here acknowledges the importance of mass gathering events (MGEs) at a time of social-economic upheaval following Covid-19.